2017
DOI: 10.5603/cj.a2016.0062
|View full text |Cite
|
Sign up to set email alerts
|

Activating mu-opioid receptors in the spinal cord mediates the cardioprotective effect of remote preconditioning of trauma

Abstract: (Cardiol J 2017; 24, 3: 314-323)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This is likely due to multiple differences including genetic and physiological homogeneity of the models, which is not a feature of human populations, physiological differences between humans and model species, human medications, and the exact timing and circumstances of MI (including the timing and location and extent of coronary occlusion). However, the basic finding that RPCT can elicit cardioprotection has been confirmed in four species to date (10,23,24,30,40), and the highly conserved neuroanatomy support that attempts should be made to translate NIC to the clinic.…”
Section: Discussionmentioning
confidence: 98%
“…This is likely due to multiple differences including genetic and physiological homogeneity of the models, which is not a feature of human populations, physiological differences between humans and model species, human medications, and the exact timing and circumstances of MI (including the timing and location and extent of coronary occlusion). However, the basic finding that RPCT can elicit cardioprotection has been confirmed in four species to date (10,23,24,30,40), and the highly conserved neuroanatomy support that attempts should be made to translate NIC to the clinic.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have documented the functional and physical interaction between adenosine and opioid receptors. Indeed, there is a cross-talk between these receptors in inducing cardioprotective effects [ 50 51 52 ]. It has been documented that adenosine may activate opioid receptors to induce cardioprotection during preconditioning [ 22 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also shown an inter-relationship between opioids and adenosine in remote preconditioning-induced cardioprotection. In this study, remote preconditioning of trauma was shown to increase the release of adenosine in the spinal cord and administration of mu-opioid receptor antagonist abolished these effects [ 52 ].…”
Section: Mechanisms Involved In Adenosine Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…of neurons in the intermediolateral nucleus of the spinal cord and the rostral ventrolateral medulla of the brainstem via the sympathetic pathway (12). The spinal cord has been implicated in the pathogenesis of cardiac injury caused by I/R (4,(13)(14)(15)(16). Furthermore, there is convincing evidence that the heart receives dense innervation from sensory afferent fibers, which peripherally release a variety of vasodilator neuropeptides, such as calcitonin gene-related peptide (CGRP) (17) and substance P (SP), in response to local stimuli (18).…”
Section: Identification Of Lncrna and Mrna Expression Profiles In Ratmentioning
confidence: 99%